2015
DOI: 10.1016/j.immuni.2015.02.010
|View full text |Cite
|
Sign up to set email alerts
|

CD5 Instructs Extrathymic Regulatory T Cell Development in Response to Self and Tolerizing Antigens

Abstract: Self-reactive T cells can escape thymic deletion and therefore some of these potentially autoaggressive T cells need to convert into regulatory T (Treg) cells to help control responses against self. However, it remains unknown how peripheral self-reactive T cells are specifically instructed to become Treg cells. We report that CD5, whose expression is upregulated in T cells by self and tolerizing antigens in the thymus and periphery, governed extrathymic Treg cell development. CD5 modified effector cell-differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
107
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(116 citation statements)
references
References 61 publications
(143 reference statements)
4
107
3
Order By: Relevance
“…A recent study showed that CD5 facilitates the extrathymic differentiation of pTreg cells by blocking mTORdependent signals induced by effector-differentiating cytokines that otherwise inhibit Treg cell induction (35). However, our results showed that Treg/Tconv differential response was not due to CD5 expression.…”
Section: Discussioncontrasting
confidence: 81%
See 2 more Smart Citations
“…A recent study showed that CD5 facilitates the extrathymic differentiation of pTreg cells by blocking mTORdependent signals induced by effector-differentiating cytokines that otherwise inhibit Treg cell induction (35). However, our results showed that Treg/Tconv differential response was not due to CD5 expression.…”
Section: Discussioncontrasting
confidence: 81%
“…Consistent with the correlation between CD5 expression and TCR signal strength, expression of CD5 is comparatively high in Treg cells (35,44). A recent study showed that CD5 facilitates the extrathymic differentiation of pTreg cells by blocking mTORdependent signals induced by effector-differentiating cytokines that otherwise inhibit Treg cell induction (35).…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…CD5 expression is notably higher in T-cell subpopulations with regulatory or suppressive functions, i.e. in regulatory T (Treg) cells [41] suggesting that it may regulate their generation and/or function [42][43][44]. Similarly, CD5 is also highly expressed by regulatory B (Breg) cells [45], in which CD5 expression is required for autocrine IL-10 production.…”
mentioning
confidence: 99%
“…In this issue of Immunity, Henderson et al (2015) show that CD5 regulates iTreg cell induction by rendering emerging iTreg cells refractory to signals mediated by effector-differentiating cytokines.…”
mentioning
confidence: 99%